The Effect of Sodium Alginate on the Absorption of Strontium and Calcium in Human Subjects - Harrison, Joan (1966)
The effect of sodium alginate on the gastrointestinal absorption of the tracers strontium-85 and calcium-47 was investigated in 19 human subjects. The tracers were administered orally with 100 mg. of a calcium carrier—calcium chloride. At the same time, sodium alginate was given in a commercial jelly. The sevenday per cent retentions of tracers were measured with a whole-body counter. After one month, the experiments were repeated without alginate so that each subject acted as his own control. Fifteen volunteers were given 1.5 g. of alginate, two were given 3.0 g. and two 0.3 g. 1.5 g. of alginate reduced the absorption of strontium by a factor of two with no significant effect on calcium absorption. The smaller dose of alginate (0.3 g.) appeared to have no effect on strontium or calcium absorption and the larger dose (3.0 g.) had no greater effect than the 1.5 g. dose.